The Sonographic Findings of Papillary Thyroid Microcarcinomas. (September 2019) - Semiz-Oysu, Aslihan; Demir, Mustafa; Kulali, Fatma; Bukte, Yasar; Oysu, Cagatay
The purpose of this research was to compare the sonographic features of papillary thyroid microcarcinomas (micro-PTCs) to those of macro-PTCs. Patients with known PTC were retrospectively reviewed and divided into micro- or macro-PTC groups, according to the largest nodule diameter, ≤10 mm or >10 mm, respectively. Eighty-nine nodules (62 macro-PTCs and 27 micro-PTCs) were evaluated. Contour irregularity was more common in micro-PTCs than macro-PTCs ( P < .05). No significant difference was found in the presence of hypoechogenicity, heterogeneity, microcalcifications, cystic component, and absence of peripheral halo between groups ( P > .05). Internal vascularity was detected in none of the micro-PTCs while being present in 13% of macro-PTCs ( P < .05). Micro-PTCs demonstrated similar sonographic findings as larger PTCs. In micro-PTCs, the presence of irregular contours, in a micro-nodule, should increase suspicion and consideration for biopsy, when clinically indicated. Internal nodular vascularity may not be present in micro-PTCs and therefore not decrease the suspicion of malignancy in the presence of other suspicious sonographic features.